Social - Psychological Aspects of the Concept of Professional Culture of Military Personnel in the System of Ensuring Public Security - Ne'matovych, Arzikulov Dilshod (Research Parks Publishers, 2023)
In this article, the need for psychological knowledge necessary for studying the social-psychological aspects of the concept of professional culture of national guard military personnel in ensuring public safety, as well as ways to improve professional culture and